Modification of a 240 kWth grate incineration system for oxyfuel combustion of wood chips. (October 2022) - Mack, A.; Maier, J.; Scheffknecht, G.
Abstract: The objective of this work is the application of the oxyfuel combustion technology for grate incineration systems to increase the CO2 concentration in the flue gas for higher efficiency when processing the gas for storage or utilization. Therefore, an experimental 240 kWth moving grate combustion facility has been modified to allow the investigation of the combustion behavior under various oxyfuel conditions. Subsequent to the modification, combustion experiments with dried wood chips under air and several oxyfuel atmospheres have been performed. During oxyfuel operation, the oxygen concentration in the gas supply streams towards the furnace has been set to 30 vol.-% dry with recycled flue gas being the rest of the gas composition. The oxygen distribution between primary and secondary zone has been varied (30%/70%, 40%/60%). Additionally, one case with increased oxygen concentration in the primary zone (40 vol.-% dry) has been investigated. The results show that oxyfuel grate incineration of the given fuel in this setup is feasible. However, the combustion behavior differs significantly between air and oxyfuel conditions in the investigated cases. The CO2 concentration in the dry flue gas could be increased to around 73 vol.-% with 5.7 vol.-% excess O2 . Compared to the reference air cases the emission rates of CO were also increased during oxyfuel operation. However, it seems manageable given enough excess oxygen (∼7 vol.-% dry). Although the temperature at the end of the furnace is comparable among the cases, oxyfuel combustion leads to lower maximum temperatures along the combustion chamber. Differences between 150 °C and 200 °C have been measured among corresponding air and oxyfuel cases. Also, the temperatures of the grate and inside the fuel bed are reduced during oxyfuel operation even in the case with increased O2 concentration leading to the impression that the thermal strain on the grate is lower compared to air operation with the same fuel throughput. Highlights: A 240 kWth pilot scale grate incineration facility with forward acting grate has been modified to enable oxyfuel combustion. Combustion behavior of wood chips differ significantly between air and oxyfuel combustion. Peak temperatures in the combustion chamber are reduced during oxyfuel operation. Oxyfuel combustion leads to lower thermal strain on the grate at the same fuel throughput.